Milletlerarası Türk folklor kongresi program ve bildiri özetleri, 23-28 Haziran 1986, İzmir- Türkiye = the third international Turkish folklore congress progamme and abstracts of papers, 23-28 June 1986, İzmir-Türkiye. (Ankara)
192 s.